Effect of light stress on maximum photochemical efficiency of photosystem II and chloroplast structure in cryptogams Cladonia mitis and Pleurozium schreberi - Dziurowicz, Patrycja; Fałowska, Patrycja; Waszkiewicz, Karolina; Wietrzyk-Pełka, Paulina; Węgrzyn, Michał (Ecological Questions, 2024)
Lichens and bryophytes are cosmopolitan organisms found in diverse environments with varying sunlight availability. However, excessive light can be a stress factor for both lichens and bryophytes, as it can damage their photosynthetic apparatus, particularly the chlorophyll a and b pigments located in the chloroplasts. The measurement of photosynthetic activity and the use of fluorescence microscopy allows the assessment of the influence of light as a stress factor on the preservation state of the thallus. The main goal of our research was to determine the changes that occur in the photosynthetic activity and structure of chloroplasts of selected species lichen Cladonia mitis (Sandst.) and moss Pleurozium schreberi (Willd. Ex Brid.) under the influence of different light intensity in laboratory conditions: FL - 100% light, RL - 30% maximum light, and NL - natural sunlight. The results of the two-factor analysis of variance (ANOVA) tests showed a variation in the activities of the selected species over time depending on the amount of light energy supplied. It was also demonstrated that soaking lichens increased their photosynthetic activity, whereas in bryophytes, it had the opposite effect, decreasing it. The microscopic results showed that Cladonia mitis showed the lowest level of chloroplast fluorescence in the strongest and reduced light, which coincides with its low level of photosynthetic activity. The mosses exhibited strong fluorescence activity of the chloroplasts, suggesting its significantly higher resistance to light radiation.